Optimum design of space trusses with buckling constraints by means of spreadsheets - Ülker, M.; Hayalio?lu, M.S. (My University, 2001)
In this paper, an algorithm is developed for the optimum design of space trusses with the help of spreadsheets. The algorithm depends on the interactive computing capability of spreadsheets. A general purpose optimization tool in spreadsheets is used for the optimization procedures. The analyses of space trusses are performed by the matrix displacement method. Specific macros have been developed for matrix calculations related to the truss systems. The displacement, tensile stress, buckling stress and minimum size constraints are considered in the formulation of the design problem. A number of design examples are presented to demonstrate the application of the algorithm. The optimum designs obtained using the spreadsheets are compared with those where a classical optimization method is employed.
Keywords: Buckling; Displacement; Optimization; Space truss; Spreadsheet